Edukasi Sit to stand exercise dengan Walker pada Pasien Stroke di Posyandu Lansia Keprabon - Taufik Eko Susilo; Arif Pristianto; Ahmada Norma Syinta; Hestia Hardani; Amalia Prasetyaningtyas; Samiyem Samiyem; Taqqiyah Nurul Azzah (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
Stroke is a blood vessel disease that is mostly caused by high blood pressure, resulting in rupture of blood vessels and bleeding in certain areas. This disease can be interpreted as a pathological condition that affects the entire body, for example paralysis, impaired cognitive function, difficulty speaking, emotional difficulties, pain and problems in daily life which cause various activity limitations for the sufferer. This of course requires appropriate medical rehabilitation that is appropriate to the condition of stroke sufferers. Medical rehabilitation is provided with the aim of optimizing and even returning the patient's body functions to normal. This rehabilitation has three main focuses, namely: medical, social and vocational rehabilitation. Stroke sufferers who are still recovering and do not receive a good rehabilitation program are certainly less able to carry out activities independently, such as from sitting to standing with balance and without the help of other people, as is found at the elderly posyandu in Keprabon Village. In the rehabilitation process, of course, family support is very necessary in helping to get optimal results. So this activity aims to provide education about sit to stand exercise to stroke sufferers and the families of sufferers at the elderly posyandu in Keprabon Village. With this physiotherapy training program activity, it is hoped that it will provide good benefits for sufferers and their families because it aims to increase the independence of stroke sufferers who are in the posyandu in Keprabon Village by increasing functional activities, especially balance in carrying out movements from sitting to standing by routinely doing sit to stand exercises. proper exercise.